1996
DOI: 10.3354/meps142147
|View full text |Cite
|
Sign up to set email alerts
|

Veligers from different populations of sea scallop Placopecten magellanicus have different vertical migration patterns

Abstract: ABSTRACT. Veligers spawned by adults collected from 3 different populations (Georges Bank, Passamaquoddy Bay and Mahone Bay, all on the northeastern coast of North America) of giant scallops Placopecten nlagellanicus were maintained for 2 mo in replicated, 9.5 m deep, polyethylene mesocosms with a 1.5"C thermal gradient at mid-depth and a 12/12 photoperiod. The populations came from varied hydrographic regimes that might require vel~gers to have different vertical migration patterns if they are to be in an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Giant scallop larvae have been shown to undertake die1 vertical migrations both in laboratory mesocosms (Silva-Serra & O'Dor 1988, Silva-Serra 1995, Gallager et al 1996, Manuel et al 1996b) and in the field (Trem- . .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giant scallop larvae have been shown to undertake die1 vertical migrations both in laboratory mesocosms (Silva-Serra & O'Dor 1988, Silva-Serra 1995, Gallager et al 1996, Manuel et al 1996b) and in the field (Trem- . .…”
Section: Discussionmentioning
confidence: 99%
“…Larvae from Georges Bank, Passamaquoddy Bay (New Brunswick), and Mahone Bay (Nova Scotia) show dissimilarities in their vertical migration behaviour in laboratory mesocosms (Manuel et al 1996b) which may be Linked to genetic differences (Manuel et al 1996a). While larvae from these 3 populations show similar settlement depth distributions in 9.5 m deep mesocosms with a 1.5"C thermocline established at a depth of 4 to 5 m (i.e.…”
Section: Vertical Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have established that larval settlement is affected by current velocity, there existing a critical range for the effectiveness of this event. Although, recently, no study could be found referring to processes involving teredinids, some investigations have focused on the importance of currents to other marine invertebrates (Hunt & Scheibling, 1996, * Author for correspondence on the recruitment of Mytilus trossolus and M. edulis; Manuel et al, 1996, on the migration of Placopecten magellanicus; and Judge & Craig, 1997, on the recruitment of Balanus eburneus). Besides the action of water currents, teredinids may guarantee their long distance dispersion through the infestation of wooden craft hulls or driftwood.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the applicability of these diel vertical migration studies to populations separated in time (daily or seasonally) and space remains unknown (e.g., Banse 1964Banse , 1986. Moreover, Manuel et al (1996) presented evidence that larvae from different populations of the same species display different vertical migration patterns.…”
Section: Biological and Physical Processes Influencing Vertical Distrmentioning
confidence: 99%